La Inserción Laboral de los Profesionales de la UNL de la carrera de Administración Pública en la Región 7. Caso de estudio graduados 2014 a 2021. - Gutiérrez Cartuche, Jhostin Andrés (2023)
The present research work aimed to analyze the level of labor insertion of professionals graduated from 2014 to 2021 of the Public Administration career of the National University of Loja in Region 7, therefore, it proceeded to carry out a situational diagnosis of public administrators, determine the level of acceptance of them in the labor sector; and establish a plan to propose improvements to the problems identified. The research was developed from a mixed, non-experimental approach, and was established as a deductive, analytical and synthetic type. The technique used is the survey, which was previously designed based on the objectives set and obtained the collaboration of 104 professionals, which provided information about their employment situation, in addition to the interview, which was applied to the president of CAPUL to obtain information on the insertion of the career in the Socio Empleo Network. Finally, the results, discussion, conclusions and recommendations of the research are presented, where 57% of the professionals graduated from the Public Administration career of the National University of Loja between 2014 and 2021 are inserted in institutions in the provinces of Loja, Zamora Chinchipe and El Oro of Region 7, therefore, it proceeded to deliver the proposal of strategies called "Plan of Improvements for the Labor Insertion of the Professionals of Public Administration of the National University of Loja in the Region 7”